2017
DOI: 10.1111/his.13261
|View full text |Cite
|
Sign up to set email alerts
|

The mutational frequency of BRAF and KRAS in low‐grade serous testicular neoplasms—a case series

Abstract: The findings of this study are in support of a role of aberrant signalling of the MAPK pathway in the pathogenesis of low-grade serous testicular neoplasms, and provide a genetic link between low-grade testicular and ovarian serous tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
7
0
3
Order By: Relevance
“…Recent studies on ovarian-type testicular tumors have focused on molecular characterization and the role of adjuvant therapy in treatment, particularly for serous tumors. In the past few years, several studies demonstrated the presence of the BRAF V600E mutation in SBTs of the testis, also seen in SBTs and lowgrade serous carcinomas of the ovary [18,28,107]. This finding provides a clear genetic association between testicular and ovarian low-grade serous neoplasms and suggests similar pathogenesis to ovarian SBTs and low-grade serous carcinomas believed to derive from Mullerian metaplasia of surface epithelium [28].…”
Section: Prospectivementioning
confidence: 79%
See 2 more Smart Citations
“…Recent studies on ovarian-type testicular tumors have focused on molecular characterization and the role of adjuvant therapy in treatment, particularly for serous tumors. In the past few years, several studies demonstrated the presence of the BRAF V600E mutation in SBTs of the testis, also seen in SBTs and lowgrade serous carcinomas of the ovary [18,28,107]. This finding provides a clear genetic association between testicular and ovarian low-grade serous neoplasms and suggests similar pathogenesis to ovarian SBTs and low-grade serous carcinomas believed to derive from Mullerian metaplasia of surface epithelium [28].…”
Section: Prospectivementioning
confidence: 79%
“…However, while the BRAF V600E mutation has been shown in testicular SBTs, it has not been extensively studied for testicular serous carcinomas. It is possible that the BRAF V600E mutation may be present in low-grade serous carcinomas, but not highgrade tumors,as their ovarian counterparts have a completely different proposed histogenesis (from fallopian tube epithelium) and molecular alterations (TP53 mutations) [28,107]. In fact, an extensive literature review showed that stratification of testicular serous carcinomas into low-and high-grade tumors is not an established practice as it is for ovarian serous carcinomas [28,107].…”
Section: Prospectivementioning
confidence: 99%
See 1 more Smart Citation
“…However, the mutational profile of such testicular tumors is poorly understood, probably due to the rarity of these entities [ 9 , 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mutational molecular profile of these tumors is poorly understood with only 5 previous cases well documented. In particular, in the serous tumor of the testis, only one previous article had suggested that like in the ovarian neoplasms, KRAS mutation could play a role in the development of these tumors [ 9 ]. Here, we report the second case of a serous borderline tumor of the testis in which a mutation of the Q61K KRAS gene is demonstrated.…”
Section: Introductionmentioning
confidence: 99%